2019
DOI: 10.1038/s41524-019-0194-z
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale self-healing mechanisms in shape memory ceramics

Abstract: Shape memory (SM) ceramics, such as yttria-stabilized tetragonal zirconia (YSTZ), are a unique family of SM materials that offer unique properties including ultra-high operating temperature, and high resistance to chemical corrosion and oxidation. However, formation of defects is usually observed in SM ceramics during manufacturing and/or by mechanical deformation. To fully take advantage of the SM properties of these ceramics, it is necessary to fully understand the nanostructural evolution of defects under e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 50 publications
0
11
0
Order By: Relevance
“…The intrinsic low k L in Mg 3 Sb 2 is mainly related to the large anharmonic scattering rate induced by the soft transverse acoustic phonon modes. [11,53] Comparing with the pure Mg 3 Sb 2 prepared using the same synthesis method, [41] the Te doping in Mg 3 Sb 2 slightly reduces the lattice thermal conductivity. With the proper Sc and Te co-doping, the lattice thermal conductivity at 300 K can be effectively reduced to 1.05 W m À1 K À1 in Mg 3.5 Sc 0.04 Sb 1.97 Te 0.03 , which decreases to 0.54 W m À1 K À1 at 725 K (see Figure 4 d).…”
Section: Angewandte Chemiementioning
confidence: 99%
See 2 more Smart Citations
“…The intrinsic low k L in Mg 3 Sb 2 is mainly related to the large anharmonic scattering rate induced by the soft transverse acoustic phonon modes. [11,53] Comparing with the pure Mg 3 Sb 2 prepared using the same synthesis method, [41] the Te doping in Mg 3 Sb 2 slightly reduces the lattice thermal conductivity. With the proper Sc and Te co-doping, the lattice thermal conductivity at 300 K can be effectively reduced to 1.05 W m À1 K À1 in Mg 3.5 Sc 0.04 Sb 1.97 Te 0.03 , which decreases to 0.54 W m À1 K À1 at 725 K (see Figure 4 d).…”
Section: Angewandte Chemiementioning
confidence: 99%
“…Recently n-type Mg 3 Sb 2 -based compounds have been intensively studied because of their outstanding TE performance as well as the low-cost and abundantly available constituent elements. [11][12][13][14][15][16][17][18][19][20][21][22][23] Exceptional n-type TE properties were first reported in Te-doped Mg 3+d Sb 1.5 Bi 0.5 with a high zT value of about 1.6 at 725 K by Tamaki et al [15] and Zhang et al, [14] in which the experimental composition and synthesis method reported by Zhang et al can be traced back to the original work by Pedersen [12] in 2012. Several reports then focused on tuning the carrier scattering mechanism through a co-doping with the transition metals on the Mg sites and Te on the Sb sites [16,17] or increasing the pressing temperature [14,19,20] in order to improve the carrier mobility at low temperatures.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A velocity term was introduced in [82] to describe the vapor transport for modeling the change in void configuration during the migration. A PFA was presented in [5] to predict the nanovoid evolution in the vicinity of an A – M interface by employing the CH–GL and mechanics equations and the effect of the mobility coefficient and the phase dependent energy barrier of nanovoids, the A – M interface width size and the transformation strain on the nanovoid evolution were investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Voids represent a misfit strain field inside the solid-gas interface. Owing to their geometry, they play the role of stress concentrators, which significantly change the mechanical driving force for different phenomena, such as dislocations generation and growth [4], PTs [5], nanovoid evolution [6], fracture [7] and more. Hence, because of their stress concentration and interfacial energy, the interaction of voids with other defects, interfaces and interphases plays an important role in kinetics, thermodynamics and nanostructures [8][9][10].…”
Section: Introductionmentioning
confidence: 99%